Analisis Literatur Tentang Efek Fotoelektrik Dan Aplikasinya Dalam Teknologi Sensor - Waruwu, Siska Natal; Harefa, Tulus Ceria (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2025)
The photoelectric effect is a phenomenon where electrons are emitted from a metal surface when exposed to light of a certain frequency. Research indicates that the kinetic energy of the emitted electrons depends on the light frequency rather than its intensity. In the context of sensor technology, the photoelectric effect is utilized in various applications such as light sensors, digital cameras, and solar panels. The use of interactive simulations, such as PhET, has proven effective in enhancing students' understanding of this concept. The analysis reveals that while students' comprehension of the photoelectric effect remains low, employing educational tools like simulations can significantly aid in physics learning and its practical applications.